Penggunaan Greenhouse dengan Atap Panel Surya dalam Optimalisasi Budidaya Semangka pada Kelompok Tani Tunas Harapan di Desa Tellumpanua Kecamatan Tanete Rilau Kabupaten Barru - AZ, Wahyul; Samsibar, Samsibar; Sukmiah, Sukmiah (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to analyze the use of a greenhouse with a solar panel roof as an effort to optimize watermelon cultivation in the Tunas Harapan Farmer Group, located in Tellumpanua Village, Tanete Rilau Subdistrict, Barru Regency. The research employed a descriptive qualitative approach through field observations, interviews, and documentation. The greenhouse functions to protect crops from extreme climate changes, while the solar panels provide an eco-friendly energy source for irrigation and temperature control systems. The findings indicate an increase in crop productivity, reduced operational costs, and improved water-use efficiency. Furthermore, this technology enhanced farmers’ awareness of renewable energy and sustainable agriculture. The implementation of solar-powered greenhouses proved to be an effective and applicable innovation to overcome climate challenges and strengthen local food security. These results are expected to serve as a reference for the development of sustainable agricultural technology in rural areas.